2017
DOI: 10.1038/srep40468
|View full text |Cite|
|
Sign up to set email alerts
|

MircoRNA-145 promotes activation of hepatic stellate cells via targeting krüppel-like factor 4

Abstract: Krüppel-like Factor 4 (KLF4), a target gene of miR-145, can negatively regulate lung fibrosis. However, the potential role of KLF4 and miR-145 in hepatic stellate cells (HSCs) activation or in hepatic fibrosis keeps unclear. This study aims to characterize miR-145 and KLF4 in activated HSCs and liver cirrhotic, and the underlying molecular basis. miR-145 was significantly up-regulated, while KLF4 was dramatically down-regulated during the activation of rat primary HSCs and TGF-βtreated HSCs. Furthermore, miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Consistent with this, in the liver fibrosis model, KLF4 expression was decreased in hepatic stellate cells [71]. In addition, according to Men and his colleague's research, KLF4 was reduced in activated hepatic stellate cells (HSCs) and cirrhotic liver tissues and KLF4 deficiency promote HSC activation [72]. Another study suggests that other mechanisms independent of IL-4 may also regulate the M2 phenotype [73].…”
Section: Discussionmentioning
confidence: 80%
“…Consistent with this, in the liver fibrosis model, KLF4 expression was decreased in hepatic stellate cells [71]. In addition, according to Men and his colleague's research, KLF4 was reduced in activated hepatic stellate cells (HSCs) and cirrhotic liver tissues and KLF4 deficiency promote HSC activation [72]. Another study suggests that other mechanisms independent of IL-4 may also regulate the M2 phenotype [73].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, microRNA-145 antagonism reverses the TGF-␤ inhibition of F508del cystic fibrosis transmembrane conductance regulator correction in airway epithelia (19). Furthermore, it was reported that miR-145 was up-regulated in activated rat primary hepatic stellate cells (HSCs) and TGF-␤-treated HSCs, which contributed to liver fibrosis (20). However, whether miR-145 regulates peritoneal fibrosis in the development of PD remains unknown.…”
Section: Peritoneal Fibrosis Is a Common Complication Of Long-term Pementioning
confidence: 99%
“…KLF4, a gut-enriched GKLF and zinc-finger transcription factor, regulates a multitude of processes in cell growth and development, proliferation and differentiation, inflammation, and apoptosis, and is even both a tumor suppressor and oncogene. A recent study reported that the expression of KLF4 declines dramatically in activated rat HSCs in the liver tissues of cirrhotic patients [34]. To determine whether KLF4 protects against CCl 4 -induced acute liver injury, a plasmid containing KLF4 was injected via tail veins 48 h prior to CCl 4 treatment.…”
Section: Discussionmentioning
confidence: 99%